Research on Two Detection Methods of Single-phase Circuit Harmonic Current Based on Simulink - 李圣清; 何政平; 李永安; 曾黎琳 (Kongzhi Yu Xinxi Jishu)
As the harmonic pollution of power grid is becoming increasingly seriously, harmonic and reactive detection has became one of the key approaches of power quality improvement. It analyzed amply a harmonic current detection method based on the two-dimensional spread theory and a fast harmonic detection method based on the active current separation theory which has no phase locked loop (PLL), and verified them by Matlab/Simulink. Simulation results show that these two methods can detect harmonic and reactive currents of single-phase circuit real-timely and accurately under ideal conditions, and the algorithms are simple and easy to implement; but once the grid voltage distorts and the fundamental frequency offsets, the harmonic current detection algorithm of single-phase circuit based on the active current separation theory has a higher accuracy.